Comparison of Hemiarthroplasty with Austin Mooreีs Prosthesis between a Standard Technique and a Minimally Invasive Technique - Sopon, Pongsak (Journal of Health Science of Thailand, 2017)
Total Hip Replacement performed through an incision less than 10 centimeters in length, has been advocated as a minimally invasive technique. Proponents have claimed that the technique reduced blood loss, postoperative pain, and length of the hospital stay, compared with a standard technique through a longer incision (15-25 cm.). The minimally invasive technique was applied in patients with fractured neck of femur, who underwent hemiarthroplasty with Austin Mooreีs prosthesis in Nakhornping Hospital, Chiang Mai. The study was aimed at comparing the clinical outcomes of the two techniques of hemiarthroplasty; the minimally invasive and the standard techniques, in patients with fractured neck of femur. Forty patients (twenty with minimally invasive technique and twenty with standard technique) who underwent hemiarthroplasty with Austin Mooreีs prosthesis during January 2003 and Febuary 2008 were included. A posterior approach was used for both techniques. Data were collected retrospectively from the hospital records. Intra-operative, initial post-operative and clinical data during hospital stay were reviewed. With the numbers of patients available, no significant differences were found between the two groups with respect to the operative time, blood loss, amount of blood transfusion, length of hospital stay. The minimally invasive technique was found to have a significantly shorter length of time that the patients able to walk with walking aid (p=0.015). There was no evidence that the minimally invasive technique resulted in less bleeding or less trauma to the soft tissues of the hip, however it would have produced a quicker recovery than the standard technique.